Development of an absorption coefficient calculation method potential for combustion and gasification simulations. (December 2015) - Yan, Linbo; Yue, Guangxi; He, Boshu
Highlights: We developed an E-EWB model to calculate the absorption coefficient. Total emissivity obtained by the EWB and LBL models will deviate at low temperature. The E-EWB model is more accurate than the EWB model. The calculation speed of the E-EWB model is about 350 times faster than that of the EWB model. The E-EWB model is prospective to be used in the CFD calculation. Abstract: Efficient and accurate calculation of the absorption coefficient is very important to the modeling of combustion and high-temperature gasification where the thermal radiation plays an important role. It is therefore important to develop a radiative absorption coefficient calculation method which is accurate enough, universal but not time consuming. In this work, a computationally efficient exponential wide band (E-EWB) model based on the exponential wide band (EWB) model is put forward and programmed so that it can be integrated into the computational fluid dynamics (CFD) software. The E-EWB calculation results are then validated against the results obtained via the line by line (LBL) model, and the runtime of this model is also evaluated. Through this work, the E-EWB model is found effective and reliable. The maximum deviation between the results obtained by the E-EWB model proposed in this work and the LBL results is within 0.8%. Moreover, the calculation speed of this model can be about 350 times faster than that of the original EWB model and is fast enough to be applied to the combustion and gasification simulations. Thus, the E-EWB model is a good choice to do the future absorption calculations during the combustion and gasification CFD simulations.